Development of a Timed Coloured Petri Nets Model for Health Centre Patient Care Flow Processes (International Journal of Engineering and Computer Science, 2015)
:Hospital deals with human lives, which are often at risk and where everything depends on quick response to diverse medical conditions. Thus, the need for efficient and effective management of patient care flow processes in a hospital is being one of the main leading goals in health sector.In this paper,a Timed Coloured Petri Nets (TCPN) formalism is used to develop a simulation model forpatient care flow processeswith emphasis on medical record area and examination room using Ladoke Akintola University of Technology Health Center, Ogbomoso, as a case study. The developed TCPN model consists of a main model (arrival and evaluation module) and a sub model (treatment module). The main model abstracts the arrival and operation(pre-treatment test) in the medical record area while the sub-model describesthe operation (treatment) taking place in the examination room of the health centre.The developed TCPN model was simulated using CPN tools while its validation was explored by comparing the simulated and actual number of patients of the health centre under study.The results obtained from the simulation of the TCPN model revealed 34 (7 inpatients and 27 outpatients), 53 (9 inpatients and 44 outpatients), 42 (8 inpatients and 34 outpatients) and 45 (9 inpatients and 36 outpatients) as the average numbers of patients entering the health centre during the first, second, third and fourth working days under consideration, respectively. Statistically, there were no significant differences between the simulated and real number of patients entering the health centre at 5% level. This gave a confirmation that the developed TCPN model accurately described the patient care flow processesof the health centre under study.The developed TCPN model could serve as a referential model for studying and improving patient care flow processesina named health centre